PENGARUH LATIHAN SELF TALK DAN IMAGERY RELAXATION TERHADAP KONSENTRASI DAN AKURASI TEMBAKAN 3 ANGKA CABANG OLAHRAGA BOLABASKET - Riyan Pratama; Bayu Hardiyono; Ahmad Muchlisin Natas Pasaribu (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2020)
Abstract. This study aims to determine the effect of self-talk and Imagery relaxation exercises on the concentration and accuracy of 3point shoot in basketball. The method used in this study was an experimental design with two groups pretest-posttest design. The subjects in this study were 12 young basketball athletes with 6 male and 6 female with purposive sampling, who were divided into two groups of experimental groups with match subject ordinal pairing (MSOP) based on the ranking of tembakan 3 angka accuracy. The instrument used is a modification of the AAHPRED basketball skill test speed spot shoot (3 point accuracy shot) and concentration grid. The data analysis technique used is  paired t test with significance level ? = 0.05. The results of this study showed (1) there is  a significant difference in the effect of exercise between self talk and Imagery relaxation exercises on concentration with each having an increase of 27.71% (self talk) and 10.97% (imagery relaxation), (2) there os significant differences  effect between self-talk and Imagery relaxation exercises in increase of  the accuracy of  tembakan 3 angka with each increase 38.61% (self talk) and 20.88% (imagery relaxation). Exercise using self talk has better benefits in increasing concentration and accuracy of tembakan 3 angka accuracy.Keyword :Self talk, imagery relaxation, concentration, tembakan 3 angka